A review of biochar-based sorbents for separation of heavy metals from water. Issue 2 (28th January 2020) - Shakoor, Muhammad Bilal; Ali, Shafaqat; Rizwan, Muhammad; Abbas, Farhat; Bibi, Irshad; Riaz, Muhammad; Khalil, Usman; Niazi, Nabeel Khan; Rinklebe, Jörg
Abstract: Biochar is the low-cost and environmental-friendly material which has shown a great potential for separation of heavy metals from water. The previous studies have established a superior role of biochar over other materials, such as activated carbon and inorganic sorbents (iron based) in efficient removal of toxic heavy metals from aqueous systems. Among the various factors influencing heavy metals sorption ability of biochar, types of feedstock/biomass and pyrolysis temperature play a significant role. The goal of this review is to increase our understanding of heavy metals sorption behavior by biochars – this is important as heavy metals sorption is driven based on biochar type, heavy metals species which involve numerous mechanisms, including the physical binding, complexation, ion exchange, surface precipitation and electrostatic interactions. In addition, this review paper describes various approaches to improve heavy metal sorption capacity of biochars by steam and acids/bases activations and impregnation of biochar-based composites with minerals, organic compounds and carbon-rich materials. The physical/chemical activation of biochars can improve the surface area, thus leading to their improved functionality, while modification/pretreatment methods help in synthesizing composites using biochar as a supporting media to develop new sorbents with efficient surface attributes for heavy metals removal from aqueous solutions.